Implementasi Fuzzy Logic Control Untuk Pemberi Pakan Ayam Otomatis Pada Ayam Broiler Dengan Menggunakan Teknologi IoT - Husyainus Sobri; Yanuar Nurdiansyah; Dwi Retno Istiyadi; Ardian Infantono (Akademi Angkatan Udara, 2021)
Implementation of Fuzzy Logic Control Method for Automatic Feeding of Broiler Chickens Using Internet of Things Technology; Husyainus Sobri, 172410102013, 2021, Information Technology Study Program, Faculty of Computer Science, University of Jember. Broiler chickens or also known as broilers are superior breeds resulting from crosses from chicken nations that have high productivity, especially in producing chicken meat. Broiler chickens are the result of cross-breeding and sustainable systems so that the genetic quality can be said to be good. Good genetic quality will appear optimally if the chicken is given supportive environmental factors, for example giving good feed so that chickens avoid death and lack of chicken weight. The use of technology in feeding chickens is an effective way to improve the quality of good chickens and avoid chicken mortality. The technology used can set the feeding time automatically and feed accordingly. To make technology work automatically, a decision-making method is needed. One suitable method is Fuzzy Logic Control. The Fuzzy Logic Control method can overcome the diversity of feeding parameters to make decisions.